Pollen grain morphology supports the taxonomical discrimination of Mediterranean oaks (Quercus, Fagaceae) (Plant Systematics and Evolution, 1983)
The exine architecture and some quantitative parameters (polar and equatorial axes and their ratio) of pollen grains allow a clear discrimination between groups of Mediterranean oak species. For the differentiation of species within groups only the quoted parameters prove useful.